Effect of salinity on callus Induction from seedling of sweet pepper Capsicum annuum L. in vitro - Jenan A. Al Ani; Zahra N. Al Hattab; Wajida K. Al Qaudhy; Ekhlas A. Al Kaaby; Ashwaq A.; Ammar K. S. (Journal of Madenat Alelem University College, 2016)
The local sweet pepper cultivar was used in this study. Sterilized seeds were growing on different germination media to germinate and obtaining seedling. Full strength MS medium supplemented with1 mg/L GA3 and agar was superior as compare to medium containing 7 gm/l agar and distilled water and MS medium with agar ,the germination percentage reached ( 86.7%) as compare to ( 55% and 23.3%) for both last two medium respectively. Moreover The results showed that the leaves gave significant differences in the fresh and dry weight of the induced calli, they were 0.248 g and 0.034 g respectively compared with 0.198 g and 0.017 g respectively for the calli produced from the hypocotyls. The results showed that the salinity had negative effect on callus growth. The control treatment with 6 ECdS.m-1 gave the highest calli fresh and dry weight 198.69 mg and 21.97 mg compared with 132.70 mg and 11.36 mg for 10 ECdS.m-1 treatments.